Bacteriophage T4 bypass31 mutations that make gene 31 nonessential for bacteriophage T4 replication: isolation and characterization. - Simon, L D (1984)
T4 bacteriophage mutants called bypass31 (byp31) that specifically suppress gene 31 amber mutations have been isolated and characterized. The mechanism by which the byp31 mutation, byp31-1, suppresses gene 31 nonsense mutations does not involve synthesis of gp31 or of a particular gp31 fragment; furthermore, the byp31 allele suppresses all nonsense mutations in gene 31 that have been tested. We detect no unusual properties among the T4 particles made in su- cells by the T4amN54byp31-1 double mutant. These virions, made in the absence of gp31, show normal heat sensitivity, normal sensitivity to osmotic shock, and normal morphology. Specific different gene 31 missense mutants are able to form plaques with high efficiencies on the following two types of host defective cells: (i) Escherichia coli groEL (Tilly et al., Proc. Natl. Acad. Sci. U.S.A. 78:1629-1633, 1981) mutants that block T4 capsid assembly and (ii) E. coli rho mutants in which T4+ heads are assembled, but in which tail production and DNA synthesis are blocked. (Note that not all rho mutants block T4 production [G. Binkowski and L. D. Simon, p. 342-350, in C. K. Mathews, E. M. Kutter, G. Mosig, and P. B. Berget, ed., Bacteriophage T4, 1983]; T4 is able to replicate in rho mutants such as rho ts15, whose principal defect is that they fail to terminate transcription.) The byp31-1 allele permits production of T4 particles in E. coli groEL host-defective mutants, but not in E. coli rho host mutants.